2023
DOI: 10.3390/biology12070942
|View full text |Cite
|
Sign up to set email alerts
|

Solute Transport across the Lymphatic Vasculature in a Soft Skin Tissue

Abstract: Convective transport of drug solutes in biological tissues is regulated by the interstitial fluid pressure, which plays a crucial role in drug absorption into the lymphatic system through the subcutaneous (SC) injection. In this paper, an approximate continuum poroelasticity model is developed to simulate the pressure evolution in the soft porous tissue during an SC injection. This poroelastic model mimics the deformation of the tissue by introducing the time variation of the interstitial fluid pressure. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Lymphatic drainage is susceptible to pressure and volume changes in the interstitium, and many studies have included the interstitium in their models (Table 1 ). Some studies modeled fluid drainage through the interstitium using Darcy’s law (Ashworth et al 2023 ; Gortberg and Romano (2023); Han et al 2023a , b ; Heppell et al 2013 , 2015 ; Ikhimwin et al 2020 ; Possenti et al 2019 ), which neglects viscous and inertial effects. However, viscous effects can be present in the interstitium under normal conditions (Moore and Bertram 2018 ).…”
Section: Existing Computational Models Of the Lymphaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphatic drainage is susceptible to pressure and volume changes in the interstitium, and many studies have included the interstitium in their models (Table 1 ). Some studies modeled fluid drainage through the interstitium using Darcy’s law (Ashworth et al 2023 ; Gortberg and Romano (2023); Han et al 2023a , b ; Heppell et al 2013 , 2015 ; Ikhimwin et al 2020 ; Possenti et al 2019 ), which neglects viscous and inertial effects. However, viscous effects can be present in the interstitium under normal conditions (Moore and Bertram 2018 ).…”
Section: Existing Computational Models Of the Lymphaticsmentioning
confidence: 99%
“…They also found that the injection depth does not affect lymphatic uptake, which contrasts with the findings of Jayathungage Don et al ( 2021 ). Following this, Han et al ( 2023b ) later improved their transport model to investigate the effects of the drug radius. Additionally, they enhanced the model’s time-efficiency, reducing the computational expense that was a limitation in the prior model, so it could be used in a clinical setting.…”
Section: Existing Computational Models Of the Lymphaticsmentioning
confidence: 99%